Часо-просторова організація "Волинської хроніки" В. Лиса - Костецька, Любов; Kostetska, Liubov (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто просторові координати в романах «волинської хро- ніки». Домінантним простором романів є Волинь як соціогеографічний, соціо- культурний, історико-політичний концепт. Хронотоп села, наявний в обох романах, відтворено як духовний простір селянина, місце, призначено Богом для життя та праці, простір, що оберігає від втрати національної і соціальної ідентичності.The article discusses the spatial coordinates in the novels of “Volyn chronicle”. Volyn is dominant space novels. It is a sociogeographical, sociocultural, historical and political concept. Chronotope of village present in both novels and reproduced as a spiritual space of the peasant. The village is a place that is intended by God to live and work. This space prevents the loss of national and social identity.Poliska dialect used in the novel. Peasant’s space is sacred space. Ukrainian space opposed totalitarian (Soviet) and the Russian Space. The space in the novel is the traditional division between “own” and “foreign”. The deformation of space is due to socio-cultural changes. Own space feels expansion of foreign space. Time-spatial parameters arise in the context of genre specificity of the novel-biographies and they are the projection of the national picture of the world in the art discourse of Ukrainian cultural space.
Time-spatial Organization of the “Volyn chronicle” of Volodymyr Lys
Keywords: хронотоп; «волинська хроніка»; роман; соло; просторові образи; сакральний простір; time-space; “Volyn chronicle”; novel; solo; space images; sacred space